2011
DOI: 10.1037/a0024783
|View full text |Cite
|
Sign up to set email alerts
|

"Recognition ROCs are curvilinear—Or are they? On premature arguments against the two-high-threshold model of recognition": Correction to Bröder and Schütz (2009).

Abstract: authors reconstructed 59 data sets from published studies in which response bias had been manipulated experimentally. These data were fit with signal detection theory (SDT) and a twohigh-threshold model (2HTM). However, the G 2 statistic for SDT fits was misspecified, and there were some errors in the reconstructed frequencies. (The authors are greatly indebted to David Kellen, who noticed these issues and cross-checked the corrections.) Below are corrected results; the authors also (a) separately analyzed rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…One explanation for this apparent discrepancy may relate to the small set of easily identifiable stimuli used in those experiments, and the use of only two memory stimuli on each trial. If participants retain representations of the identities and locations of stimuli presented in the memory array, even when the bindings between these features are lost-as suggested by Cali et al (2015)-this may allow them to respond to a memory test with an informed guess about the nature of the relevant binding (see, e.g., Rhodes, Cowan, Hardman, & Logie, 2018 for evidence of informed guessing in tests of visual WM). Further, if the distractor stimulus is sometimes mistaken for a memory stimulus, this would reduce the success of such a guessing process.…”
Section: How Does Novelty Affect Distractor Interference?mentioning
confidence: 99%
“…One explanation for this apparent discrepancy may relate to the small set of easily identifiable stimuli used in those experiments, and the use of only two memory stimuli on each trial. If participants retain representations of the identities and locations of stimuli presented in the memory array, even when the bindings between these features are lost-as suggested by Cali et al (2015)-this may allow them to respond to a memory test with an informed guess about the nature of the relevant binding (see, e.g., Rhodes, Cowan, Hardman, & Logie, 2018 for evidence of informed guessing in tests of visual WM). Further, if the distractor stimulus is sometimes mistaken for a memory stimulus, this would reduce the success of such a guessing process.…”
Section: How Does Novelty Affect Distractor Interference?mentioning
confidence: 99%
“…As a result, the following discussion of empirical ROCs focuses on distinguishing between threshold MPT and continuous SDT models. Schütz (2009, 2011) conducted a meta-analysis^ of 62 studies that reported binary ROCs from memory tasks, and they collected new data in three experiments to more clearly address the issue. Empirical ROCs.…”
Section: Receiver Operating Characteristicsmentioning
confidence: 99%